Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan - Nur Azhana@ Bazilah Binti Haji Mohamad, Siti; Farhana Binti Haji Shahlehi , Syahnur; Siti Nor Suriana Binti Haji Talip , Hajah (Fakultas Ekonomi dan Bisnis Islam, 2024)
Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan